The trypanotolerance network. 1. Objectives, organization and current activities - Trail, J.C.M.; Murray, M.; Wissocq, Y.J.; D'Ieteren, G.D.M.; Paling, R.W.; Leak, S.G.A.; Moloo, S.K.; Maehl, H.M. (OAU/STRC, 1985)
Evaluates the productivity of different breeds of cattle, sheep and goats, particularly trypanotolerant breeds, exposed to different degrees of tsetse challenge under various management systems in 9 West and Central African countries and in three associated East African countries, w. the objectives of improving livestock production in tsetse infested areas.